Crescere nella migrazione. Generi e sessualità fra gli adolescenti di origine straniera - Federica Tarabusi (EtnoAntropologia)
How do the children of immigrants define and represent themselves in the Italian society? How do they build and negotiate their own subjectivity of women/men and experience their sexual bodies in adolescence? In what way their everyday experiences are different from (or similar to) those of Italian teenagers?